2001
DOI: 10.1046/j.1365-2133.2001.04219.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of fractalkine at sites of inflammation: antigen-presenting cells in psoriasis express high levels of fractalkine

Abstract: The results of this study confirm that fractalkine is upregulated at sites of inflammation. Thus, it is likely that this molecule plays a key part in cell trafficking. An increased expression of fractalkine at the dermal papillae provides a plausible explanation for the migration and accumulation of T cells at these sites in psoriasis. Earlier studies have reported an increased number of dermal dendrocytes in psoriatic tissue; however, the functional role of these cells in the pathogenesis of psoriasis is larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Multiple reparative processes were affected by the receptor, including inflammation, fibrosis, neovascularization, and regeneration of parenchymal cells. The results are consistent with previous reports showing that the CX3CL1-CX3CR1 ligand-receptor pair plays an important role in the initiation and progression of inflammation (12)(13)(14), and is up-regulated in inflammatory diseases (20 -23, 26, 27, 42), including inflammatory diseases of the skin (15,16,19). Our data linking CX3CR1 to fibrosis in skin wound healing are consistent with a report of CX3CL1 and CX3CR1 expression in the skin and lung of patients with systemic sclerosis (16), and an in vivo study showing that CX3CR1 KO mice have reduced collagen accumulation and renal fibrosis in a model of ischemia-reperfusion injury (18).…”
Section: Discussionsupporting
confidence: 82%
“…Multiple reparative processes were affected by the receptor, including inflammation, fibrosis, neovascularization, and regeneration of parenchymal cells. The results are consistent with previous reports showing that the CX3CL1-CX3CR1 ligand-receptor pair plays an important role in the initiation and progression of inflammation (12)(13)(14), and is up-regulated in inflammatory diseases (20 -23, 26, 27, 42), including inflammatory diseases of the skin (15,16,19). Our data linking CX3CR1 to fibrosis in skin wound healing are consistent with a report of CX3CL1 and CX3CR1 expression in the skin and lung of patients with systemic sclerosis (16), and an in vivo study showing that CX3CR1 KO mice have reduced collagen accumulation and renal fibrosis in a model of ischemia-reperfusion injury (18).…”
Section: Discussionsupporting
confidence: 82%
“…Since expression of FKN and expression of CX3CR1 can be induced by immune cells, studies have focused on the role of FKN as an inflammatory mediator. Indeed, FKN is up-regulated in the inflammatory site of rheumatoid arthritis (12,18), inflammatory bowel disease (19), atherosclerosis (20), psoriasis (21), myositis (22), and various inflammatory conditions of the kidney (23) and brain (24), although FKN gene-disrupted mice did not show significant differences from wild-type mice in either steady-state or inflammatory conditions (25).…”
Section: F Ractalkine (Cx3cl1 Fknmentioning
confidence: 99%
“…17 It is involved in many skin inflammatory diseases 18 such as psoriasis, eczema and atopic dermatitis, and is associated with the terminal cutaneous nerve [nerve growth factor (NGF) receptor positive]. 19 Using our model and various activity tests, we demonstrated that chemokine action is endothelial cell origin-selective. On the one hand, CCL21 and CX3CL1 specifically induced a T4 activated cell line (CEMT4) lymphocyte adhesion on human peripheral lymph node endothelial cells, clone B3 (HPLNEC.B3), and human appendix endothelial cells (HAPEC), respectively, whereas CXCL12 and CCL5 did not display any specific action.…”
Section: Introductionmentioning
confidence: 99%